Effectiveness Test of Methanol, Ethyl Acetate, and Chloroform Fractions of Bidara Leaf Extract (Zizyphus mauritiana L.) on Wound Healing in Rabbits (Oryctolagus cuniculus) - Umarella, Novel; Wirasti, Wirasti; Slamet, Slamet; Waznah, Urmatul (Biology, Medicine, & Natural Product Chemistry, 2024)
Bidara (Zizyphus mauritiana L.) contains alkaloids, glycosides, saponins, flavonoids, terpenoids, phenols, and the best antioxidant properties of its leaves. In bidara leaf, they are antibacterial, antiviral, and antiseptic, play a role in cell regeneration and repair, so they are effective in wound healing. This study aimed to determine the effectiveness of bidara leaf extract fractions on incision wounds and determine which fraction was more effective in narrowing the incision wound. Making wounds on rabbits (Oryctolagus cuniculus) using the Morton method, by making an incision on the back with a diameter of 2 cm. Testing the effectiveness of fractions in wound healing with rabbits divided into 5 groups, namely positive control, negative control, methanol fraction (MeOH), ethyl acetate fraction (Ethac), and chloroform fraction (CHCl3) with a dose of 100 mg/KgBB rabbit in 1 ml of solvent. The diameter of the wound area was measured using the Macbiophotonic Image J program, and the data were analyzed using One Way Anova (ANOVA) followed by the Tukey test. The results of data analysis using the ANOVA method with a significant value of 0,004 (p<0,05). The conclusion of the results of the research conducted for 8 days shows that the MeOH, Ethac, and CHCl3 fractions of bidara leaf extract have the effectiveness of wound healing in rabbits with differences in healing shown by the Ethac fraction with a better effect than the MeOH and CHCl3 fractions.